Autodeterminação local e desenvolvimento: uma análise da dinâmica social no município de São Roque de Minas - Gava, Rodrigo (2009)
In this thesis, the basic research of Chase and Simon (1973) is questioned, and we seek new results by analyzing the errors of experts and beginners chess players in experiments to reproduce chess positions. Chess players with different levels of expertise participated in the study. The results were analyzed by a Brazilian grandmaster, and quantitative analysis was performed with the use of statistical methods data mining. The results challenge significantly, the current theories of expertise, memory and decision making in this area, because the present theory predicts piece on square encoding, in which players can recognize the strategic situation reproducing it faithfully, but commit several errors that the theory can¿t explain. The current theory can¿t fully explain the encoding used by players to register a board. The errors of intermediary players preserved fragments of the strategic situation, although they have committed a series of errors in the reconstruction of the positions. The encoding of chunks therefore includes more information than that predicted by current theories. Currently, research on perception, trial and decision is heavily concentrated on the idea of 'pattern recognition'. Based on the results of this research, we explore a change of perspective. The idea of 'pattern recognition' presupposes that the processing of relevant information is on 'patterns' (or data) that exist independently of any interpretation. We propose that the theory suggests the vision of decision-making via the recognition of experience.